Attitudes of Human Resources in the Department of Education in Al-Kharj Governorate Towards Blended Training - Al-Dossary, Noura Sultan; Al-Shehri, Ajlan Mohammad (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the trends of human resources in the education administration in Al-Kharj Governorate towards blended training, and the obstacles that hinder the use of blended training in administration, and to find ways to overcome the obstacles that impede the use of blended training in administration. To achieve the objectives of the study and answer its questions, the descriptive analytical approach was employed, the target population of the study was the administrative employees in the Education Department in Al-Kharj Governorate, who numbered (2000) employees. The sample size in the study was (322), and the questionnaire was used as a tool for collecting information, he results of the study showed that there is a lack of agreement among the study individuals on the reality of the use of blended training in the education administration in Al-Kharj Governorate from the point of view of the human resources staff. Complete agreement among the study individuals on the human resources trends in the education administration in Al-Kharj Governorate towards integrated training, and there is complete agreement among the study individuals on the obstacles that impede the use of blended training in the education administration in Al-Kharj Governorate. The study recommended ensuring the creation of appropriate training venues for the application of blended training, in terms of training methods, and the provision of services that meet the needs of human resources staff.